The funeral kit mortuary practices in the archaeological record - Baker, Jill L., 1964- (Walnut Creek, Calif. : Left Coast Press, 2012)
"Studies of mortuary archaeology tend to focus on difference--how the researcher can identify age, gender, status, and ethnicity from the contents of a burial. Jill L. Baker's innovative approach begins from the opposite point: how can you recognize the commonalities of a culture from the "funeral kit" that occurs in all burials, irrespective of status differences? And what do those commonalities have to say about the world view and religious beliefs of that culture? Baker begins with the Middle and Late Bronze Age tombs in the southern Levant, then expands her scope in ever widening circles to create a general model of the funeral kit of use to archaeologists in a wide variety of cultures and settings. The volume will be of equal value to specialists in Near Eastern archaeology and those who study mortuary remains in ancient cultures worldwide"--
Machine generated contents note: List of Figures Preface Chapter 1: Introduction Chapter 2: The Archaeology of Death and Burial: Established Interpretations, Terminologies and Definitions Chapter 3: The Funeral Kit Model Chapter 4: Beyond the Model: The Funeral Kit in Wider Canaan (Middle Bronze IIB/C-Late Bronze Age II) Chapter 5: The Genesis and Extinction of the Funeral Kit in Canaan Chapter 6: Beyond Canaan: The Funeral Kit in Wider Geographical and Chronological Contexts Chapter 7: Theory and Practice Chapter 8: The Ties That Bind References Index About the Author.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Funeral rites and ceremonies -- Cross-cultural studies; Death -- Social aspects -- Cross-cultural studies; Human remains (Archaeology) -- Cross-cultural studies; Ethnoarchaeology; Electronic books